Pengaruh Harga dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan pada Restoran Gula Padi di Kota Garut - Akmal Husna; Wati Susilawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research investigates how Price and Service Quality affect Customer Loyalty through Customer Satisfaction at Gula Padi Restaurant. The study employs a descriptive quantitative approach, employing Structural Equation Modeling (SEM) through SmartPLS for analyzing data. A total of 100 respondents, all customers of Gula Padi Restaurant in Garut City, were chosen through purposive sampling. The criteria for selection included having made at least one purchase within the past month and residing in Garut City. Data were gathered directly via a questionnaire utilizing a 1–5 Likert scale. The results reveal that enhancements in Price and Service Quality significantly contribute to the development of Customer Satisfaction. In turn, Customer Satisfaction is essential for developing Customer Loyalty. Within the tested model, Customer Satisfaction acts as a mediating variable that channels the effects of Price and Service Quality onto Customer Loyalty. Practically, these findings offer guidance for Gula Padi Restaurant management in Garut City to design pricing strategies and optimize services that enhance satisfaction while building customer loyalty. Moreover, this research can act as a foundation for upcoming research by integrating extra variables  or extending the investigation to other culinary sectors.